Peran Mahasiswa dalam Kuliah Kerja Nyata (Kukerta) Kelompok 44 UIN SMH Banten dalam Pelestarian Lingkungan dan Kepedulian Pendidikan Desa Cibojong (Jurnal Pelayanan Masyarakat, 2025)
Community Service (Kukerta) is a form of student community service that aims to apply knowledge, build social awareness, and encourage positive change in the surrounding environment. This article discusses the role of Kukerta Group 44 students from UIN Sultan Maulana Hasanuddin Banten in environmental conservation efforts and increasing educational awareness in Cibojong Village, Serang Regency. The majority of the population in Cibojong Village earn their living as farmers, but the agricultural produce obtained is generally only sufficient to meet daily needs, without guaranteeing long-term economic sustainability. Therefore, students educate the community through guidance from the BPP (Agricultural Extension Center), about learning to farm for the long term, and invite them to join the farming community. In addition, the community’s education level is relatively low, with most children only completing elementary school. Through a participatory approach and qualitative descriptive methods, students implement various programs such as planting productive trees, waste management education, and socialization of sustainable agriculture. In the field of education, students hold tutoring activities, motivational classes, and literacy for village children and adolescents. The results of the activity show that the active involvement of students has a positive impact on increasing public awareness of the importance of protecting the environment and continuing education. Kukerta is an effective means of building collaboration between universities and village communities to address local challenges sustainably.